Lifestyle Interventions vs. Multi Interventional Therapy on Physiological Parameters of Metabolic Syndrome among Women: A Comparative Study - A. J. Elizabeth; J Aruna; P. J. Mercy (Wolters Kluwer Medknow Publications, 2024)
Background: Metabolic syndrome is one of the emerging health issues in developing countries. It includes diabetes, high Blood Pressure (BP), obesity, and elevated blood cholesterol. Materials and Methods: This comparative study was conducted from March 2019 to February 2020 in selected areas of Ernakulam district, Kerala. The study used a quasi-experimental design with a nonequivalent control group. One-way analysis of variance and paired t-tests were used for statistical analysis. Women (aged between 35 and 55 years) with metabolic syndrome were recruited by multistage sampling (N = 220) and randomly assigned into three groups: (a) control, (b) Lifestyle Interventions (LI), and (c) Multi Interventional Therapy (MIT). LI was given to the LI group, and reflexology foot massage along with LI was given to the MIT group for 12 weeks. The control group received routine care. Physiological variables were assessed before and after the intervention. Results: Women who received MIT and LI had significantly lower values of weight, Body Mass Index (BMI), and waist circumference after the treatment from baseline and compared with control (F = 12.09, 15.58, 22.37, p < 0.001). A remarkable change in systolic and diastolic BP was found in the MIT group (pretest mean of systolic BP and diastolic BP in control: 142.3 and 90.1, LI: 141.7 and 89.7, MIT: 141.8 and 89.8, p = 0.945, posttest means control: 142.6 and 90.4, LI: 131.5 and 85.5, MIT: 118.5 and 78.3, (F = 54.83, 57.87, p < 0.001). Conclusions: Both LI and MIT should be considered as interventions for reducing the physiological parameters of metabolic syndrome, such as body weight, BMI, and obesity. MIT was found to be more effective in reducing blood pressure.